Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1016/j.visres.2006.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual filling-in from the edge of the blind spot

Abstract: Looking at the world with one eye, we do not notice a scotoma in the receptor-free area of the visual field where the optic nerve leaves the eye. Rather we perceive the brightness, color, and texture of the adjacent area as if they were actually there. The mechanisms underlying this kind of perceptual filling-in remain controversial. To better understand these processes, we determined the minimum region around the blind spot that needs to be stimulated for filling-in by carefully mapping the blind spot and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 35 publications
5
39
2
1
Order By: Relevance
“…Two and three objects below the blind spot appear as three and four objects, respectively. The phenomenon differs in the following two unique aspects from perceptual filling-in of dots at the blind spot reported in previous studies (Brown and Thurmond 1993;Kawabata 1982;Spillmann et al 2006): it occurred even when (a) the objects were large enough to be counted, and (b) the objects were presented on only one side of the blind spot.The first aspect suggests that the visual system produces an independent illusory object in the blind spot. The previous studies have shown that visual information consisting of small dots of an uncountable size, which could be considered as a texture, filled-in the blind spot (Brown and Thurmond 1993;Spillmann et al 2006).…”
contrasting
confidence: 65%
See 2 more Smart Citations
“…Two and three objects below the blind spot appear as three and four objects, respectively. The phenomenon differs in the following two unique aspects from perceptual filling-in of dots at the blind spot reported in previous studies (Brown and Thurmond 1993;Kawabata 1982;Spillmann et al 2006): it occurred even when (a) the objects were large enough to be counted, and (b) the objects were presented on only one side of the blind spot.The first aspect suggests that the visual system produces an independent illusory object in the blind spot. The previous studies have shown that visual information consisting of small dots of an uncountable size, which could be considered as a texture, filled-in the blind spot (Brown and Thurmond 1993;Spillmann et al 2006).…”
contrasting
confidence: 65%
“…Two and three objects below the blind spot appear as three and four objects, respectively. The phenomenon differs in the following two unique aspects from perceptual filling-in of dots at the blind spot reported in previous studies (Brown and Thurmond 1993;Kawabata 1982;Spillmann et al 2006): it occurred even when (a) the objects were large enough to be counted, and (b) the objects were presented on only one side of the blind spot.…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…The spanning of the scotoma by the target is thought to be an important prerequisite for perceptual filling-in to occur. 14,15 …”
Section: Methodsmentioning
confidence: 99%
“…Ela apresentou erros geralmente com grande variabilidade e os erros médios eram desprezíveis em certas condições, sugerindo-se que havia preenchimento perceptivo sem distorção de tamanho. Em outras condições, os erros médios eram significativamente diferentes de zero, sugerindo-se que havia preenchimento perceptivo com distorção de tamanho, similar aos dados relatados por Araragi e Nakamizo (2008) e Spillmann et al (2006). Uma possível explicação para essa variação é a hipótese da interpolação neural da mancha cega proposta por Fiorani, Rosa, Gattass e Rocha-Miranda (1992).…”
Section: Relação Entre O Erro Constante E a Extensão Da Mancha Cegaunclassified